Analysis of Marketing Mix Strategies in Increasing Sales Volume of Tempong Food Stall Surabaya - Pratama, Rifqi Agata Geovani; Prabowo, Budi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to identify the marketing strategies used by Kedai Tempong Surabaya to increase sales volume. The sampling method was carried out purposively by evaluating the implementation of the 7P marketing mix strategy (product, price, place, promotion, people, physical evidence, process). This study was analyzed using a qualitative descriptive approach and SWOT analysis (Strength, Weakness, Opportunity, Threat). SWOT analysis is used to assess the company's internal strengths and weaknesses as well as opportunities and threats from the external environment. With SWOT analysis, several alternative effective decision-making strategies can be produced. The results showed that Kedai Tempong Surabaya has an internal strength of 2.25, weaknesses of 0.71, opportunities of 1.53, and threats of 1.33. Based on the SWOT analysis diagram, Kedai Tempong Surabaya is in quadrant 1, which supports an aggressive growth strategy (growth-oriented strategy) to increase sales turnover.